2012
DOI: 10.1371/journal.pone.0047624
|View full text |Cite
|
Sign up to set email alerts
|

Decay of Genes Encoding the Oomycete Flagellar Proteome in the Downy Mildew Hyaloperonospora arabidopsidis

Abstract: Zoospores are central to the life cycles of most of the eukaryotic microbes known as oomycetes, but some genera have lost the ability to form these flagellated cells. In the plant pathogen Phytophthora infestans, genes encoding 257 proteins associated with flagella were identified by comparative genomics. These included the main structural components of the axoneme and basal body, proteins involved in intraflagellar transport, regulatory proteins, enzymes for maintaining ATP levels, and others. Transcripts for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 68 publications
0
20
0
Order By: Relevance
“…By selecting the best hit with >97% identity, 7,862 T30-4 genes were matched to the array data. Expression calls from Affymetrix MAS 5.0 software were normalized before analysis, resulting in values that showed good concordance with data from SybrGreen reverse transcription-qPCR studies ([62]; Additional file 2). Analyses of changes during development and variance calculations used per-gene normalized data, set to a mean of 1.0.…”
Section: Methodsmentioning
confidence: 88%
“…By selecting the best hit with >97% identity, 7,862 T30-4 genes were matched to the array data. Expression calls from Affymetrix MAS 5.0 software were normalized before analysis, resulting in values that showed good concordance with data from SybrGreen reverse transcription-qPCR studies ([62]; Additional file 2). Analyses of changes during development and variance calculations used per-gene normalized data, set to a mean of 1.0.…”
Section: Methodsmentioning
confidence: 88%
“…infestans ranged from 4.1 to 39.8% (Fig 2B; Table 1). To help assess these preliminary tests, we examined the expression of the genes encoding effector Avr3A and haustorial protein Hmp1 which are markers of biotrophic growth, Npp1 which is a marker of necrotrophic growth, and a flagella-associated centrin which is a marker of sporulation [3, 30]. In both leaves and tubers, Avr3A and Hmp1 mRNAs were >10-fold higher in the leaf and tuber samples at 3 dpi than 6 dpi (Fig 2B).…”
Section: Resultsmentioning
confidence: 99%
“…Pathogens accomplish this through mechanisms that include manipulating hosts to shift nutrients to sites of infection, generating feeding structures, expressing transporters for the nutrients, and making metabolic enzymes for assimilating the nutrients [13]. Studies in fungi and bacteria have identified transporters and metabolic pathways that contribute to pathogenesis [410].…”
Section: Introductionmentioning
confidence: 99%
“…Analyses across the breadth of eukaryotic diversity indicate that the role of PKs in flagella is not universal, however. While all PK-bearing eukaryotes (animals, alveolates, choanoflagellates, excavates and stramenopiles) contain flagella or cilia, our current and prior (Judelson et al, 2012) searches of genome databases indicate that the reverse is not true: groups with flagellated life-stages that lack PK genes include chytrids, amoeba and lower plants, e.g. Batrachochytrium, Acanthamoeba and Chlamydomonas respectively.…”
Section: Discussionmentioning
confidence: 75%
“…In prior studies of the potato late blight pathogen Phytophthora infestans, we identified genes encoding PKs (Kim and Judelson, 2003;Randall et al, 2005). The premise that these may help maintain energy homeostasis in zoospores was supported by our discovery that genes encoding PKs were absent from the azoosporic oomycete Hyaloperonospora arabidopsidis (Judelson et al, 2012). Biochemical analyses subsequently indicated that the phosphagen in Phytophthora is taurocyamine (Uda et al, 2013).…”
Section: Introductionmentioning
confidence: 96%